Characterization of a broad-spectrum antifungal strain, Streptomyces graminearus STR-1, against Magnaporthe oryzae - Shen, Wenyuan; Liu, Renju; Wang, Jiazheng; Yang, Maolan; Qi, Tuo; Shu, Guosong; He, Min; Chen, Xuewei (Frontiers in Microbiology, 2024)
Fungal diseases such as the devastating rice blast pose severe threat to crop production worldwide.Biological control of crop diseases caused by fungal pathogens is an environment-friendly approach for safeguarding crop production. But the insufficient availability of microbial agents effective against various fungal diseases has hampered the development of green production in crop. In this study, we identified a broad-spectrum antifungal bacterium Streptomyces graminearus STR-1 showing antagonistic activity to diverse fungal pathogens including Magnaporthe oryzae, Rhizoctonia solani, Fusarium graminearum, Ustilaginoidea virens and Bipolaria maydis. Its antifungal activity was relatively stable and less affected by temperature and pH. Evaluation of the biocontrol activity of STR-1 revealed that STR-1 prevented and controlled rice blast disease via eliciting plant immunity and suppressing fungal infection-structure development. STR-1 broth extract inhibited the spore germination likely through inhibiting protein synthesis. Combing LC-MS and chromatography analysis of the antimicrobial compounds purified from STR-1 broth extract, together with decoding STR-1 genomic sequence, we identified 4-oxo-4-[(1-phenylethyl)amino]but-2-enoic acid, 1,3,5-Trimethylpyrazole and SMA-1 as the potential main STR-1 secondary metabolites associated with its antifungal effects. This study suggests that bacterial strain STR-1 can be used for identifying highly effective and broad-spectrum secondary metabolites for containing rice blast disease and other crop diseases. The application of the active compounds offers a promising measure to tackle fungal disease.